Evolution of sediment temperature, pressure, phases distribution, carbon pools and seabed methane flux at the Arctic continental Shelves since the Last Glacial Maximum - Kehua You (Zenodo, 2023)
This dataset are produced bya manuscript ( Biodegradation of Ancient Organic Carbon Fuels Seabed Methane Emission at the Arctic Continental Shelves )to be submitted to the Journal of Geophysical Research - Global Biogeochemical Cycles. I The file "MethaneEmission_Permafrost" contains the predicted temperature, pressure, pore water salinity, ice stable zone, methane hydrate stable zone, ice saturation, methane hydrate saturation, free methane gas saturation, labile organic carbon content, stable organic carbon content, and methanogenesis rate from seafloor to 1200 m depth from 18,000 years before present to 2,000 years after present for 8 different simulation scenarios. The file "Seabed_Methane_Flux" contains the predicted seabed methane emission rate from18,000 years before present to 2,000 years after present for 8 different simulation scenarios. Detailed information about the model could be found in the paper Biodegradation of Ancient Organic Carbon Fuels Seabed Methane Emission at the Arctic Continental Shelves.